2005
DOI: 10.1088/0022-3727/38/2/001
|View full text |Cite
|
Sign up to set email alerts
|

Structure modification of 0–3 piezoelectric ceramic/polymer composites through dielectrophoresis

Abstract: Anisotropic material properties can be induced in ceramic-polymer composites by applying an alternating electric field of moderate strength during processing. Under suitable conditions, particles of a ceramic filler material that are randomly dispersed in a liquid polymer or pre-polymer can be polarized and they then exhibit a collective response to localised gradients in the electric field. Typically the particles experience a mutually attractive force which causes them to form 'pearl-chains' or columnar stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 11 publications
2
74
0
1
Order By: Relevance
“…composites. This value is more than one order of magnitude higher than that obtained for randomly dispersed particle composites [17][18][19][20][21][22][23][24][25][26][31][32][33][34][35] and on par with the values reported for the piezoelectric polymers PVDF and P(VDF-TrFE). [14][15][16] The explanation for the increase in g 33 is that d 33 strongly depends on the intra-chain connectivity, while ε r is a bulk property, proportional to the fill factor but almost independent of the microstructure.…”
Section: Fabrication Of Knln-pdms Composite Filmsmentioning
confidence: 67%
See 1 more Smart Citation
“…composites. This value is more than one order of magnitude higher than that obtained for randomly dispersed particle composites [17][18][19][20][21][22][23][24][25][26][31][32][33][34][35] and on par with the values reported for the piezoelectric polymers PVDF and P(VDF-TrFE). [14][15][16] The explanation for the increase in g 33 is that d 33 strongly depends on the intra-chain connectivity, while ε r is a bulk property, proportional to the fill factor but almost independent of the microstructure.…”
Section: Fabrication Of Knln-pdms Composite Filmsmentioning
confidence: 67%
“…[22][23][24] Aligned composite films have been reported with piezoelectric voltage coefficients attaining 120 mV m N -1 . [25,26] The Curie temperature remains, in first order approximation, that of the ceramic filler.…”
Section: Introductionmentioning
confidence: 99%
“…Chains which are free to move (i.e., not bound to one of the electrodes) are attracted towards other chains during later stages of the dielectrophoresis process; a phenomenon seen before in DEP processed composites. 24 The average orientation angleh and relative average chain length,L L max , as a function of time for a typical experiment are represented in Figure 6. Here, L max is defined as the length of the microscope image in the direction of the electric field.…”
Section: Alignment Of Multiple Fibersmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] It is demonstrated that dielectrophoresis can be used for structuring of PZT particles as columns in a polymer matrix, resulting in composites with quasi 1-3 connectivity. [16][17][18][19] This will keep the manufacturing process as simple as 0-3 composites, and consequently, production costs can be kept low. In dielectrophoresis, when a moderate electric field is applied across a suspension of ferroelectric particles in an insulating medium, the particles orient themselves toward the direction of applied electric field.…”
Section: Introductionmentioning
confidence: 99%